СIRCULATING SECRETORY IMMUNOGLOBULINA IN SEPTIC DISORDERS - N. V. Mal'tseva (SPb RAACI, 2018)
Insufficiency of local immunity can play an important role in pathogenesis of sepsis, including septic (acute) infectious endocarditis (IE). The paper presents data on secretory immunoglobulin A (sIgA) contents in blood serum of patients with sepsis (26 women and 32 men), acute (11 women and 23 men) and subacute (7 women and 13 men) IE, depending on localization of the infection site (angiogenic or non-angiogenic), outcome of the disease and carriage of glutathione-S-transferase P1 gene variants (GSTP1Ile105Val). A control group consisted of 25 women and 24 men without hypertension and ischemic heart disease and lacking evidence of focal and systemic infection, was examined. Laboratory studies were performed with еnzyme immunoassay and allele-specific polymerase chain reaction. We have found that, despite large individual variability of serum sIgA concentration in sepsis and infectious endocarditis, the majority of patients had a significant (on average, 4-fold) IgA increase against controls, in both men and women, especially in acute IE (a mean of 5-fold over control values). Subacute infectious endocarditis is associated with lesser sIgA in circulation than acute IE and sepsis, which may be used for early differential diagnosis of these conditions. There were no gender differences in sIgA contents. In sepsis with non-angiogenic source of infection, the sIgA levels were higher than in angiogenic infection. There was no association of sIgA level with survival (mortality), which excludes this index from predictive markers in sepsis and IE. Carriage of heterozygous GSTP1Ile105Val genotype increases the risk of sepsis and IE development, regardless of clinical course, and homozygous genotype GSTP1Ile105Ile is associated with higher contents of circulating immunoglobulin than in carriers of GSTP1Val105Val genotype. Thus, a wide range of individual variability in of circulating sIgA levels in patients with sepsis and infective endocarditis may be connected with location of infection source and genetic factors.